2017
DOI: 10.1007/s10495-017-1437-4
|View full text |Cite
|
Sign up to set email alerts
|

Caspase cleavage of transcription factor Sp1 enhances apoptosis

Abstract: Sp1 is a ubiquitous transcription factor that regulates many genes involved in apoptosis and senescence. Sp1 also has a role in the DNA damage response; at low levels of DNA damage, Sp1 is phosphorylated by ATM and localizes to double-strand break sites where it facilitates DNA double-strand-break repair. Depletion of Sp1 increases the sensitivity of cells to DNA damage, whereas overexpression of Sp1 can drive cells into apoptosis. In response to a variety of stimuli, Sp1 can be regulated through proteolytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 76 publications
3
17
0
Order By: Relevance
“…Interestingly, previous studies have reported that bortezomib induces the activation of caspase-8 (Liu et al, 2007;Laussmann et al, 2011;Amodio et al, 2012;Bullenkamp et al, 2014;Bat-Erdene et al, 2016) and bortezomib-mediated Sp1 degradation is blocked by FMK-ZEITD (Bat-Erdene et al, 2016). A role for caspase-3-dependent cleavage of Sp1 has also been reported (Torabi et al, 2018). The inhibition of bortezomib-induced effects by FMK-ZEITD is consistent with the observed induction of caspase-8 in MM cells (ANBL-6 and RPMI 8226) ( Fig.…”
Section: Bortezomib Decreases Expression Of Sp Transcription Factors supporting
confidence: 86%
“…Interestingly, previous studies have reported that bortezomib induces the activation of caspase-8 (Liu et al, 2007;Laussmann et al, 2011;Amodio et al, 2012;Bullenkamp et al, 2014;Bat-Erdene et al, 2016) and bortezomib-mediated Sp1 degradation is blocked by FMK-ZEITD (Bat-Erdene et al, 2016). A role for caspase-3-dependent cleavage of Sp1 has also been reported (Torabi et al, 2018). The inhibition of bortezomib-induced effects by FMK-ZEITD is consistent with the observed induction of caspase-8 in MM cells (ANBL-6 and RPMI 8226) ( Fig.…”
Section: Bortezomib Decreases Expression Of Sp Transcription Factors supporting
confidence: 86%
“…pLXSN-Sp1-30N (182 N-terminal peptide sequence) was constructed from pLXSN-Flag-Sp1-HA. pLZS-Sp1-30N (Torabi et al, 2018) and Sp1 point mutants were constructed from pLZS-Flag-Sp1. Sp1-30N was constructed by inserting Sal1 restriction sites adjacent to codon 183 of the Sp1 sequence using PCR and the following primers: Forward (5 0 CCC ACA GTT CCA GAC CGT CGA CGG GCA ACA GCT GCA G 3 0 ) and Reverse (5 0 CTG CAG CTG TTG CCC GTC GAC GGT CTG GAA CTG TGG G 3 0 ).…”
Section: Resource Availabilitymentioning
confidence: 99%
“…Among the many proteins involved in recognition of DSBs is specificity protein 1 (Sp1), which has also been implicated in DSB repair (Beishline et al, 2012;Fletcher et al, 2018;Olofsson et al, 2007). Sp1 is ubiquitously expressed and best known as a transcription factor that regulates genes involved in DNA repair, apoptosis, and cell proliferation (Black et al, 2001;Deniaud et al, 2009;Torabi et al, 2018). Sp1's activity is regulated by (A) U2OS cells were pretreated with 10 mM BrdU for 3 h to label cells in the S phase (blue).…”
Section: Introductionmentioning
confidence: 99%
“…Specific protein 1 (Sp1) is one of the earliest identified transcription factors (Beishline and Azizkhan-Clifford 2015). The abnormal activation of Sp1 could up-regulate the expression of tumor related factors and angiogenic factors, thus providing a good microenvironment for tumor growth, and promoting the proliferation, metastasis and angiogenesis of colon, gastric and pancreatic tumors and regulate apoptosis (Beishline and Azizkhan-Clifford 2015;Liu et al 2018;Torabi et al 2018). Sp1 could interact with the promoter of vascular endothelial growth factor A (VEGFA), and up-regulate its expression, which promotes the proliferation of vascular endothelium, angiogenesis and vascular permeability, thus promoting the growth and metastasis of tumor via binding with VEGF receptor 2 (VEGFR2) (Chen et al 2018;Vizcaino et al 2015).…”
Section: Introductionmentioning
confidence: 99%